2021
DOI: 10.51847/rzqepcg
|View full text |Cite
|
Sign up to set email alerts
|

Cost minimization of cardiovascular disease (CVD) drugs in primary healthcare centers in Bandung, Indonesia

Abstract: This is an open access journal, and articles are distributed under the terms of the Creative Commons Attribution-Non Commercial-ShareAlike 4.0 License, which allows others to remix, tweak, and build upon the work non-commercially, as long as appropriate credit is given and the new creations are licensed under the identical terms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…In a study, Rano K. sinuraya et al revealed that the Cost related to CVD in all primary health care centers in Bandung is higher after the implementation of national health insurance [10].…”
Section: Introductionmentioning
confidence: 99%
“…In a study, Rano K. sinuraya et al revealed that the Cost related to CVD in all primary health care centers in Bandung is higher after the implementation of national health insurance [10].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, desert dust events and major anthropogenic resources disrupt air quality in different parts of the country (Farsani et al 2018). Air pollution has been reported to contribute to respiratory and cardiovascular diseases, asthma attacks, acute bronchitis and decreased lung function, which can increase hospitalization rate (Sinuraya RK, et. al., 2021;Alzahrani S, et.…”
Section: Introductionmentioning
confidence: 99%
“…With a wide range in types and relatively high and increasing prevalence in the global population, cardiovascular diseases have attracted in recent years the attention of many experts and researchers in this field (Sinuraya, R. K., et. al., 2021;Alzahrani, S., et.…”
Section: Introductionmentioning
confidence: 99%